The cult of the KOI - Tamadachi, Michugo (T.F.H. Publications, 1990)
The book is an excellent reference for beginners and experts as well. It gives a great overview of the history of Japanese, Domestic and German Koi. It gives an excellent review of the different types of Koi that have help me a great deal in identification.